Financial Market Anomalies: Evidence from Tunisia Stock Market - Ahmed, Bouteska; Boutheina, Regaieg (Asian Journal of Empirical Research, 2017)
The aim of this study is to investigate the presence of seasonal market anomalies (calendar anomalies) and to analyze their effects on the behavior of financial investors in terms of decisions and profit on the Tunisian market during the entire period that starts on January 2003 and ends on 31 December 2015. This work examines four calendar effects which are the new week of the year (WOY), the day of the week (DOW), the week of the month (WOM) and month of the year (MOY) effects using daily data of Tunisian Stock Market Index (TUNINDEX closing price) and dummy variables based on a GARCH (1,1) regression model adopted by Levy and Yagil (2012) to demonstrate whether the anomalies exist on the Tunisian market. The findings show that the returns for Friday are always positively significant. In contrast, the returns for October are almost negatively significant and low compared to other months. We also find that market calendar anomalies are clues to help investors improving their trading strategies and timing their investments to make abnormal profits.